M3 Pseudomonas aeruginosa induces inflammation in bronchial epithelial cells via the p38 MAP and Syk tyrosine kinase pathways. (12th November 2019) - Coates, MS; Ito, K; Alton, EWFW; Davies, JC
Abstract : Objectives: Pseudomonas aeruginosa ( Pa ) infection is a major cause of inflammation in cystic fibrosis airways, initially mediated by bronchial epithelial cells, which are vital for the immune response. Kinase activation, such as MAP and Tyrosine kinases, are integral to inflammatory responses to Pa, therefore are potential targets for novel anti-inflammatory therapies. This study aims to determine which kinases are involved in Pa -induced inflammation. Methods: BEAS-2B bronchial epithelial cells were treated with kinase inhibitors against p38 MAPK (p38), MEK, JNK, Syk and c-Src at 1 µg/ml, for 2 hours, followed by Pa infection at 2.5 × 10 7 CFU/ml, for 5 hours. CXCL8 and IL-6 release were measured by sandwich ELISA. Combinations of inhibitors and novel narrow spectrum kinase inhibitors (NSKI) against p38, Src and/or Syk kinases were used to investigate synergistic effects of blocking multiple pathways. Synergy of compound combinations was calculated using the Chou-Talalay method. Results: An inhibitor of p38 showed 85.8% (p<0.05) and 74.7% inhibition of CXCL8 and IL-6, respectively, and a Syk inhibitor showed 99.5% (p<0.0001) and 100% (p<0.05) inhibition, respectively. MEK and JNK kinase inhibitors showed little inhibition of CXCL8 or IL-6, and the c-Src inhibitor inhibited CXCL8 only. Combinations of p38 and Syk/c-Src inhibitors showed synergistic inhibition of CXCL8, but not IL-6. An NSKI targeting p38, Src and Syk kinases showed significant inhibition of CXCL8 at 0.1 µg/ml (101%, p<0.01) and IL-6 at 0.001 µg/ml (100%, p<0.01), demonstrating greater potency than the single inhibitors alone. Conclusion: Pa -induced CXCL8 and IL-6 release is highly dependent on both p38 and Syk kinases, and inhibition of multiple selected pathways can lead to synergistic effects. Further investigation is planned to elucidate the possible role of Syk kinase in p38 activation. This study shows a potential for inhibitors of multiple specific kinases as potent anti-inflammatory therapies.